2022
DOI: 10.1136/thorax-2022-218929
|View full text |Cite
|
Sign up to set email alerts
|

Performance of QuantiFERON-TB Gold Plus assays in paediatric tuberculosis: a multicentre PTBNET study

Abstract: RationaleIn 2016, a new interferon-gamma release assay (IGRA) was introduced, QuantiFERON-TB Gold Plus (QFT-Plus), claimed to have improved sensitivity in active tuberculosis (TB).ObjectivesThis study aimed to determine the performance of QFT-Plus, compared with previous generation IGRAs and the tuberculin skin test (TST), in children with TB in Europe.MethodsMulticentre, ambispective cohort study within the Paediatric Tuberculosis Network European Trials Group (ptbnet), a dedicated paediatric TB research netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 33 publications
0
12
0
1
Order By: Relevance
“…Half of the children 5–11 years of age and the majority of children 12–16 years of age were tested with an IGRA. IGRA is considered more specific in children with previous BCG immunisation but sensitivity is comparable as shown in a recent multicentre study from Europe [19]. As known from other Swiss studies, most of the children with TB disease in Switzerland are of foreign origin [8] and many of them have been vaccinated with Bacillus Calmette-Guérin, which is associated with the risk of a false-positive TST [20].…”
Section: Discussionmentioning
confidence: 93%
“…Half of the children 5–11 years of age and the majority of children 12–16 years of age were tested with an IGRA. IGRA is considered more specific in children with previous BCG immunisation but sensitivity is comparable as shown in a recent multicentre study from Europe [19]. As known from other Swiss studies, most of the children with TB disease in Switzerland are of foreign origin [8] and many of them have been vaccinated with Bacillus Calmette-Guérin, which is associated with the risk of a false-positive TST [20].…”
Section: Discussionmentioning
confidence: 93%
“…This study reported that QFT-Plus did not have improved sensitivity compared with QFT-GIT in the overall population or in children less than 1 year of age but did have improved sensitivity in immunocompromised children (75.0% vs. 59.6%, respectively). 40 Further evidence is needed to better define the sensitivity of QFT-Plus versus QFT-GIT in different pediatric populations.…”
Section: Discussionmentioning
confidence: 99%
“…Neither test discriminates ATB from LTBI, nor are they licensed for ATB diagnosis. Yet, they are widely used to facilitate the diagnosis of ATB with sensitivity reaching 77-85% 10 . The new version of QFT test, QuantiFERON-TB Gold Plus, has so far exhibited similar properties to previous-generation IGRAs in children in both ATB and LTBI 10 .…”
mentioning
confidence: 99%